The Effects of Plant Age and Harvesting Time on Chicoric and Caftaric Acids Content of E. purpurea (L.) Moench: Chicoric and caftaric acids content of E. purpurea - Maryam Shekarchi; Homa Hajimehdipoor; Mahnaz Khanavi; Arezoo Roostaie (Iranian Journal of Pharmaceutical Sciences, 2012)
Plants of Asteraceae are used in traditional medicine and phytotherapy. The two main caffeic acid derivatives, chicoric and caftaric acid which are found in many genus of Asteraceae including Echinacea exhibit important biological activities. The level of these acids in E. purpurea is affected by many factors such as growing situations, extraction methods, storage conditions and plant age. In this investigation, chicoric acid and caftaric acid content in aerial parts and roots of E. purpurea harvested in spring and summer from 1-, 2- and 3-years old plants cultivated in Iran were determined by using HPLC method. The results revealed that maximum level of chicoric acid achieved in aerial parts of 1- and 2-years old plants beside 2-years old roots collected in spring. Aerial parts of 1- and 2-years old plants harvested in spring had maximum content of caftaric acid as well. It is concluded that total parts of 2-years old E. purpurea harvested in spring can be a good source of caffeic acid derivatives and used for preparation of the plant products.